Anomalous structural dynamics of minimally frustrated residues in cardiac troponin C triggers hypertrophic cardiomyopathy. Issue 21 (29th April 2021) - Marques, Mayra A.; Landim-Vieira, Maicon; Moraes, Adolfo H.; Sun, Bin; Johnston, Jamie R.; Dieseldorff Jones, Karissa M.; Cino, Elio A.; Parvatiyar, Michelle S.; Valera, Isela C.; Silva, Jerson L.; Galkin, Vitold E.; Chase, P. Bryant; et al.
Abstract : Cardiac TnC (cTnC) is highly conserved among mammals, and genetic variants can result in disease by perturbing Ca 2+ -regulation of myocardial contraction. Abstract : Cardiac TnC (cTnC) is highly conserved among mammals, and genetic variants can result in disease by perturbing Ca 2+ -regulation of myocardial contraction. Here, we report the molecular basis of a human mutation in cTnC's αD-helix ( TNNC1 -p.C84Y) that impacts conformational dynamics of the D/E central-linker and sampling of discrete states in the N-domain, favoring the "primed" state associated with Ca 2+ binding. We demonstrate cTnC's αD-helix normally functions as a central hub that controls minimally frustrated interactions, maintaining evolutionarily conserved rigidity of the N-domain. αD-helix perturbation remotely alters conformational dynamics of the N-domain, compromising its structural rigidity. Transgenic mice carrying this cTnC mutation exhibit altered dynamics of sarcomere function and hypertrophic cardiomyopathy. Together, our data suggest that disruption of evolutionary conserved molecular frustration networks by a myofilament protein mutation may ultimately compromise contractile performance and trigger hypertrophic cardiomyopathy.